Mikania micrantha Kunth leaf Methanol Extract as Bioherbicide Againts The Growth of Amaranthus spinosus L. Weeds - Parwati, Heni; Mukarlina, Mukarlina; Linda, Riza (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
The presence of weeds on plantation land causing a decrease in growth and productivity of cultivated plants. Thorny amaranth (Amaranthus spinosus L.) is broadleaf weeds that have high competitiveness. This study aims to determine the influence of the application of bitter vine (Mikania micrantha Kunth) leaf extracts against the growth of thorny amaranth and the best concentration that can inhibit the growth of thorny amaranth weed. This study has been carried out for October 2023 - March 2024 in the Biology Screen House and Chemistry Laboratory, Faculty of Mathematics and Natural Sciences, Tanjungpura University. This study used a completely randomized design (CRD) with four levels concentration treatment of bitter vine leaf extracts with five replications. The treatment consisted of bitter vine leaf extract with a concentration 0% (0g/ml) as a control, 15% (0,15 g/ml), 20% (0,2 g/ml) and 25% (0,25 g/ml). Data was analysed using Kruskal Wallis test followed by Mann-Whitney test. The results showed giving bitter vine leaf extracts can inhibited the growth of thorny amaranth weeds. Application of bitter vine leaf extract concentration 15% was the best treatment that can inhibited the growth of thorny amaranth on parameters weeds height (2,53 cm), number of leaves (2,65 strands), root length (1,74 cm), wet weight (0,13 grams) and dry weight (0,01 grams).